HUBUNGAN KEPATUHAN TIM BEDAH DALAM PELAKSANAAN SURGICAL SAFETY CHECKLIST DENGAN PASIEN SAFETY DI IBS RSUD Dr. HARYOTO LUMAJANG - Wicaksono, Dedi; Sunanto, Sunanto; Mashuri, Mashuri (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2023)
The compliance of the surgical team in carrying out the Surgical Safety Checklist (SSC), when time out phase, is a very important part to achieve patient safety during operative procedures. The purpose of this study was to analyze the correlation between the compliance of the surgical team and the implementation of SSC in the operating room. The design used in this study was Spearman rank with a sample size of 39 respondents who were observed once using a total sampling technique based on inclusion and exclusion criteria. The data collection method was carried out observationally on the compliance of the surgical team using the 2009 WHO guidelines and the SSC implementation using the 2015 NPSG guidelines. Data processing in this study used the correlation coefficient frequency distribution. Observation results from the compliance of the surgical team showed that most of the respondents had a level of compliance (94.9%) and less compliance (5.1%), and for patient safety, it was obtained data that most of the patients were safe as many as 35 (89.7%) and 4 (10.3%) were unsafe while based on the table it was found that the p value was less than α (0.05), namely 0.000, this figure indicated that H0 was rejected and H1 was accepted, which means that there is a relationship between surgical team compliance in the implementation of SSC with patient safety and the Spearman correlation value of 0.688 indicates a strong correlation.